Close Relationships and Happiness across Cultures (Cross-Cultural Advancements in Positive Psychology, 2018)
This volume focuses explicitly on close relationships as a reliable source for individual happiness and well-being across cultures. The work in this volume addresses theoretical issues and presents new cross-cultural data in the study of close relationships and happiness. Experts from different parts of the world provide in-depth, authoritative reviews and new findings on the relationship between various types of close bonds (e.g., intimate, marital, friendship, grandparent) and happiness in a variety of cultures. An ideal resource for researchers and students of relationship science and positive psychology, this rich, clear, and up-to-date book serves as an important reference for academicians in related fields of psychology such as cross-cultural, social, and developmental.